2019
DOI: 10.18203/2349-2902.isj20192400
|View full text |Cite
|
Sign up to set email alerts
|

Coronary cameral fistula to right atrium in a 10 year old male: a case report

Abstract: A coronary cameral fistula is a rare cardiac anomaly and involves an abnormal communication between one of the coronary arteries and a cardiac chamber. In most of cases, it is a congenital lesion and is asymptomatic in early life. Once symptoms appear, patient warrants early evaluation and treatment. Presently, CT Angiography is the best investigation for diagnosing the disease and the best treatment modality is surgical closure. We present a case of a 10 year old male with large coronary cameral fistula from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…5 In the case report of a 10-year-old child with a fistula from the RCA to RA, the child presented with dyspnea on exertion and palpitation. 6 Adult patients may have exertional dyspnea, orthopnea, paroxysmal nocturnal dyspnea, chest pain, and fatigue which arise out of coronary steal phenomenon or diastolic overload. Conduction abnormalities like atrial fibrillation and ventricular tachyarrhythmias are also reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In the case report of a 10-year-old child with a fistula from the RCA to RA, the child presented with dyspnea on exertion and palpitation. 6 Adult patients may have exertional dyspnea, orthopnea, paroxysmal nocturnal dyspnea, chest pain, and fatigue which arise out of coronary steal phenomenon or diastolic overload. Conduction abnormalities like atrial fibrillation and ventricular tachyarrhythmias are also reported.…”
Section: Discussionmentioning
confidence: 99%
“…5 Banday et al reported a case of a 10-year-old male child in which the coronary cameral fistula was between proximal RCA and RA. 6 Minhas et al reported a case of fistula in a 49-year-old woman, connecting the LAD and the first obtuse marginal artery to the LV. 7 Gill and Sood reported the case of a 77-year-old female patient where the fistula was between the LAD and the LV.…”
Section: Discussionmentioning
confidence: 99%
“…These may be acquired from trauma, infection, or iatrogenic injury. [ 1 5 6 7 ] Coronary fistulas with the cardiac chambers (Cameral fistulas) are rare congenital vascular anomalies reported in approximately 0.08% to 0.3% of unselected patients undergoing diagnostic coronary angiography. [ 8 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…The concern during cardiopulmonary bypass is to maintain adequate perfusion to the myocardium beyond the fistula. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%